2022
DOI: 10.1002/ajoc.202200564
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Molecular Oxygen Assisted Laccase Catalyzed Sustainable Organic Transformations

Abstract: Bio‐catalysis is a versatile and powerful tool in organic synthesis, hazardous chemical remediation, biosensors, and industrial sectors. It has been claimed that laccases can function as an intriguing class of biocatalyst in organic chemistry. They are highly favourable catalysts and offer advantages over conventional oxidants and toxic metal catalysts by exhibiting high activity in aqueous media under mild conditions and also work on diverse functional groups possessing substrates maintaining the atom economy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 130 publications
0
3
0
Order By: Relevance
“…Currently, new methodologies appearing on sustainable catalysts for the recovery of the catalyst. These methods encompass heterogeneous metal catalytic systems reactivity, selectivity, recyclability, and catalytic activity, as well as the mechanistic pathway of desired product formation, the removal of multiple organic dyes by using biomass-derived functionalized graphene aerogels [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, new methodologies appearing on sustainable catalysts for the recovery of the catalyst. These methods encompass heterogeneous metal catalytic systems reactivity, selectivity, recyclability, and catalytic activity, as well as the mechanistic pathway of desired product formation, the removal of multiple organic dyes by using biomass-derived functionalized graphene aerogels [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…4 → 5a , Scheme 2A). 9 After this, Deska et al reported that C. fumago chloroperoxidase ( Cfu CPO), catalyzes the Achmatowicz reaction on a range of substrates and with moderate enantioselectivity. 10 A subsequent study by the same group utilized Cfu CPO, assisted by glucose oxidase (GOx), for the generation of peracid from an acetic acid buffer, for Achmatowicz reactions of the type 4 → 5b (Scheme 2B).…”
Section: Introductionmentioning
confidence: 99%
“…These intermediates can oxidize the target substrate at a high rate. The use of laccase-mediator systems (LMS) in various areas is extensively covered in the literature [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%